Meta-analysis of dynamic contrast enhancement and diffusion-weighted MRI for differentiation of benign from malignant non-mass enhancement breast lesions - Zhang, Jing; Li, Longchao; Zhang, Li; Zhe, Xia; Tang, Min; Lei, Xiaoyan; Zhang, Xiaoling (Frontiers in Oncology, 2024)
Purpose: The objective of this study was to conduct a meta-analysis comparing the diagnostic efficacy of models based on diffusion-weighted imaging (DWI)-MRI, dynamic contrast enhancement (DCE)-MRI, and combination models (DCE and DWI) in distinguishing benign from malignant non-mass enhancement (NME) breast lesions. Materials and methods: PubMed, Embase, and Cochrane Library were searched, from inception to January 30, 2023, for studies that used DCE or DWI-MRI for the prediction of NME breast cancer patients. A bivariate random effects model was used to calculate the meta-analytic sensitivity, specificity, and area under the curve (AUC) of the DCE, DWI, and combination models. Using subgroup analysis and meta-regression analysis to find the source of heterogeneity. Results: Of the 838 articles screened, 18 were eligible for analysis (13 on DCE, 5 on DWI, and four studies reporting the diagnostic accuracy of both DCE and DWI). The funnel plot showed no publication bias (P > 0.5). The pooled sensitivity and specificity, as well as the AUC of DCE, DWI, and combination model were 0.58, 0.72, and 0.70, respectively, and 0.84, 0.69, 0.84, respectively, and 0.88,0.79,0.90, respectively. The meta-analysis found no evidence of a threshold effect and significant heterogeneity among tials in term of DCE sensitivity and specificity, as well as DWIspecificity alone (I2> 75%) . The meta-regression revealed that different diagnostic criteria contributed to the DCE study’s heterogeneity (P < 0.05). Different reference criteria significantly influenced the heterogeneity of the DWI model(P < 0.05). Subgroup analysis revealed that clustered ring enhancement (CRE) had the highest pooled specificity(0.92) among other DCE features. The ADC with a mean threshold <1.3×10−3 mm2/s has a slightly higher sensitivity of 0.86 compared to 0.82 with an ADC of ≥1.3×10−3mm2/s. Conclusion: The combination model (DCE and DWI) outperforms DCE or DWI alone in identifying benign and malignant NME lesions. The DCE-CRE feature was the most specific test for ruling in NME cancers.